The Cambridge companion to life and death - Luper, Steven (Cambridge : Cambridge University Press, 2014)
This volume meets the increasing interest in a range of philosophical issues connected with the nature and significance of life and death, and the ethics of killing. What is it to be alive and to die? What is it to be a person? What must time be like if we are to persist? What makes one life better than another? May death or posthumous events harm the dead? The chapters in this volume address these questions, and also discuss topical issues such as abortion, euthanasia, and suicide. They explore the interrelation between the metaphysics, significance, and ethics of life and death, and they discuss the moral significance of killing both people and animals, and the extent to which death harms them. The volume is for all those studying the philosophy of life and death, for readers taking applied ethics courses, and for those studying ethics and metaphysics more generally.
Introduction / Steven Luper -- The nature of life / Mark A Bedau -- The nature of people / Eric T. Olson -- Persistence and time / Katherine Hawley -- The malleability of identity / Marya Schechtman -- The nature of human death / David Degrazia -- Assess lives / Noah Lemos -- On the length of a good life / Eyjölfur K. Emilsson -- Mortal harm / John Martin Fischer -- When do we incur mortal harm? / Jens Johansson -- The symmetry problem / James Warren -- Posthumous harm / Simon Keller -- Life's meaning / Steven Luper -- Enhancing humanity / Nicholas Agar -- Procreating / David Archard -- Abortion / Michael Tooley -- Killing ourselves / Thomas E. Hill, Jr. -- Killing in self-defense / Kadri Vihvelin -- Imperfect aiding / Matthew Hanser -- Killing and extinction / Krister Bykvist.
Title from publisher's bibliographic system (viewed on 09 Nov 2015).
Keywords: Life; Death